DETERMINANTS OF MALNUTRITION AMONG CHILDREN IN RURAL FARM HOUSEHOLDS IN OGUN STATE, NIGERIA - Ogunnaike, Maria; Kehinde, Mojisola; Olabode, Olubunmi (FUDMA JOURNAL OF SCIENCES, 2021)
Malnutrition in children is one of the most serious public health problems in Nigeria and also in the world. Therefore, the objective of the study was to measure the prevalence of stunting, wasting and underweight and to assess the socio economic factors that influence the anthropometric indicators among children residing in rural farm households of Ogun State Nigeria.  A cross sectional study was employed and 206 farm households were interviewed using a structured, personally administered questionnaire consisting of socio-demographic factors, maternal characteristics, farm production characteristics and anthropometric measurement was used to gather data for 100 children. Nutri-survey, SPSS and Stata software was used to perform descriptive statistics and logistic regression analyses. The summary statistics of nutritional status of children in the study area revealed that the prevalence of stunting, underweight and wasting was 70%, 25 % and 8%, respectively. In view of World Health Organisation recommendation into two age disaggregated groups, male children were found to be more stunted and wasted than females in the study area. Age(p<0.05) and sex of the child(p<0.05), Farm size(p<0.01), household size(p<0.05), access to safe water(p<0.05), years of formal education of the household head (p<0.05) and access to health services (p<0.01) are factors that significantly affect the incidence of stunting, underweight and wasting in the study area. Thus, efforts should be made to improve the health services and also provision of safe water to farm households for reducing malnutrition among children.